Compositional Gradients in Gramineae Genes - Wong, Gane Ka-Shu (Cold Spring Harbor Laboratory Press, 2002)
In this study, we describe a property of Gramineae genes, and perhaps all monocot genes, that is not observed in eudicot genes. Along the direction of transcription, beginning at the junction of the 5′-UTR and the coding region, there are gradients in GC content, codon usage, and amino-acid usage. The magnitudes of these gradients are large enough to hinder the annotation of the rice genome and to confound the detection of protein homologies across the monocot–eudicot divide.